PENGARUH BEBAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP KEPUASAN KERJA KARYAWAN PT. THOYYIBATUL RIZKI PEKANBARU - Hardiansyah Diki; Marzolina Marzolina; Wasnury Rendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The purpose of this study was to analyze the effect of workload and organizationalcommitment on employee job satisfaction. The population in this study were allemployees totaling 40 people. The sample used in this study is a saturated sample.Data were analyzed using multiple linear regression analysis techniques. Theresults of data analysis show that workload has a significant negative effect onemployee job satisfaction, organizational commitment has no effect on employeejob satisfaction. Employee job satisfaction can be increased by paying attention toworkload and organizational commitment. The organization is expected toimprove the level of workload and increase the organizational commitment thathas been implemented within the organization. Keywords: Workload, Organizational Commitment, Employee Satisfaction